Kajian Kebutuhan Rumah di Kota Palu - Farid, Muhammad (Jurnal Sains dan Teknologi Tadulako, 2025)
The need for housing along with clothing and food is a primary human need, meaning that everyone needs a house or a place to live. On September 28, 2018 there was an earthquake with a magnitude of 7.4 on the Richter Scale (SR), followed by a tsunami and liquefaction. The consequences of this disaster affected housing and settlements in Palu City. This study aims to determine the backlog and characteristics of the backlog in Palu City. This type/type of research uses a quantitative descriptive approach. Data collection methods through observation, literature studies, interviews, questionnaires and documentation. In this study the data analysis techniques used were occupancy backlog analysis and descriptive statistical analysis. From the results of this study it is known that the backlog of occupancy in Palu City includes East Palu District 9,558 units, West Palu 4,911 units, South Palu 2,687 units, Ulujadi 659 units and Tawaeli 656 units while Tatanga, Mantikulore and North Palu Districts do not have a backlog, in other words the number the available houses are sufficient, and from the results of the backlog characteristic analysis on the price variable the average indicator value is 3.25, the location variable the average indicator value is 3.56 and the facilities variable the average indicator value is 3.11 this shows the attitude of the people in The City of Palu wants improvements and adjustments to policies related to prices, location and housing facilities that currently exist in the City of Palu.